2017
DOI: 10.1002/cmdc.201700047
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Chemistry Profiling of Monocyclic 1,2‐Azaborines

Abstract: The first examples of biologically active monocyclic 1,2-azaborines have been synthesized and demonstrated to exhibit not only improved in vitro aqueous solubility in comparison to the corresponding carbonaceous analogues, but in the context of a CDK2 inhibitor, also improved biological activity and better in vivo oral bioavailability. This proof-of-concept study establishes the viability of monocyclic 1,2-azaborines as a novel pharmacophore with distinct pharmacological profiles that can help address challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 50 publications
0
59
0
2
Order By: Relevance
“…Similar considerations can be made for one of the smallest possible nitrogen‐containing compounds with such a property, aminoborane (H 2 N−BH 2 ; Figure ). The B−N scaffold has been discussed as C=C surrogate because of its isoelectronic character . However, it has been shown early on that the B−N rotational barrier (29.3 kcal mol −1 ) of aminoborane is much smaller than that of the C=C bond in ethylene (62.5 kcal mol −1 ) .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Similar considerations can be made for one of the smallest possible nitrogen‐containing compounds with such a property, aminoborane (H 2 N−BH 2 ; Figure ). The B−N scaffold has been discussed as C=C surrogate because of its isoelectronic character . However, it has been shown early on that the B−N rotational barrier (29.3 kcal mol −1 ) of aminoborane is much smaller than that of the C=C bond in ethylene (62.5 kcal mol −1 ) .…”
Section: Figurementioning
confidence: 99%
“…In the excited state, the conformation resulting from a 90° rotation around the B−N bond is not the lowest in energy, though. Further relaxation by pyramidalization is more favored owing to negative hyperconjugation resulting in a twisted out‐of‐plane arrangement of the amine . Based on this, we designed a system that would allow favoring an electronic transition to one specific conformer in the excited state (Figure ).…”
Section: Figurementioning
confidence: 99%
“…Several of the new functionalization methods described above allowed the synthesis of BN isosteres of biologically active molecules (Scheme ). Recently, Liu et al reported on the medicinal chemistry profiling of three BN isosteres of biologically active carbonaceous biphenyl carboxamides ( 28a – c ) (Scheme ) . The compounds were prepared from the BN isostere of non‐steroidal anti‐inflammatory drug felbinac by amide‐coupling in the presence of 2‐chloro‐4,6‐dimethoxy‐1,3,5‐triazine/ N ‐methylmorpholine.…”
Section: 12‐azaborininesmentioning
confidence: 99%
“…TheB ÀNs caffold has been discussed as C=Cs urrogate because of its isoelectronic character. [9][10][11][12][13][14] However,i th as been shown early on that the B À Nr otational barrier (29.3 kcal mol À1 ) [2,15] of aminoborane is much smaller than that of the C = Cb ond in ethylene (62.5 kcal mol À1 ). [3,15] Interestingly,a nalogous behavior has been observed for aminoborane theoretically [4,16] as well as experimentally.…”
mentioning
confidence: 99%